The Making of a Montane Taro Garden - Manuel Boissière (The Ethnobiological Society of Indonesia, 2021)
Taro (Colocasia esculenta) is an essential crop in Papua New Guinea, especially in the highlands where taro grows at high altitudes (above 2,000 m) and sweet potato is absent. Taro and its cultivation are part of the collective memory of the Oksapmin society, in Sandaun province. The creation, maintenance, and harvest of a taro garden follow elaborate techniques and rules, the knowledge of which is not universal among villagers. This article describes the making of a taro garden by Oksapmin cultivators. The process is divided into two parts: activities related to the “mother garden”, where cuttings for the garden-to-be must be harvested, along with activities and techniques involved in preparing the new taro garden. The author discusses the significance of taro gardens in Oksapmin society.